PENGGUNAAN MEDIA PERMAINAN ULAR TANGGA TERHADAP KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS III SDN SIMOMULYO 8 SURABAYA - Nawang Wulan, Annisa; Noviardani Kartika Prameswari; Alfina Citrasikmawati; Suhartini Nurul Azminah; Mira Pradipta Ariyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics education learning in elementary schools still faces problems in the form of low student learning activeness due to the lack of variation in learning media used by teachers. The learning process tends to be dominated by lecture-based methods and limited instructional media, causing students to become passive and less actively involved. This study aims to describe the use of the snakes and ladders game as a learning medium and students’ learning activeness in Grade III Mathematics education on whole number arithmetic operations. This research employed a descriptive qualitative approach with a case study design. The research subjects consisted of 27 third-grade students of SDN Simomulyo 8 Surabaya. Data collection techniques included observation, interviews, and documentation, while data analysis was carried out through data reduction, data display, and conclusion drawing. Data validity was ensured through technique triangulation. The results showed that the use of the snakes and ladders game media was able to create a more active, interactive, and enjoyable learning atmosphere. Students demonstrated increased learning activeness, as indicated by higher enthusiasm, active participation in discussions, strong learning motivation, and sustained focus during the learning process. The snakes and ladders game media also supported teachers in delivering learning materials in a more creative and innovative manner. Therefore, the snakes and ladders game media can be used as an effective alternative learning medium to enhance students’ activeness and learning motivation in elementary school Mathematics education.